English Furniture and its Setting : From the later sixteenth to the early nineteenth century - Brett, Gerard, 1915-1968 (Book collections on Project MUSE., 1965)
This book, which will be valuable to all those interested in English furniture, undertaken by a newly apoointed Curator in the course of becoming familiar with the materials in his charge.